2020
DOI: 10.5152/tao.2020.5382
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Resection of Sinonasal and Nasopharyngeal Pleomorphic Adenomas: A Case Series

Abstract: Owner and Responsible Manager on behalf of the Turkish Otorhinolaryngology Head and Neck Surgery Society / Türk Kulak Burun Boğaz ve Baş Boyun Cerrahisi Derneği adına Sahibi ve Sorumlu Yazı İşleri Müdürü: Özgür YİĞİT •

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…The mean age of patients with intranasal PA is 45.4 years ( 1 ); however, our patient was much older, 72 years of age. The most frequent symptom in these patients at presentation is unilateral nasal obstruction, as in our case, but they can also present with epistaxis, nasal mass, cheek or nasal swelling, external deformity, mucopurulent rhinorrhea, and epiphora ( 1 - 4 ).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The mean age of patients with intranasal PA is 45.4 years ( 1 ); however, our patient was much older, 72 years of age. The most frequent symptom in these patients at presentation is unilateral nasal obstruction, as in our case, but they can also present with epistaxis, nasal mass, cheek or nasal swelling, external deformity, mucopurulent rhinorrhea, and epiphora ( 1 - 4 ).…”
Section: Discussionmentioning
confidence: 53%
“…Malignant transformation of PA has been reported, meaning carcinoma ex PA and malignant mixed tumor ( 1 , 2 , 4 ). The diagnosis of benign metastasizing PA of the salivary gland is extremely rare and still under debate ( 1 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 20% of all pleomorphic adenoma originates from the minor salivary gland and among them, pleomorphic adenoma of the nasopharynx is uncommon [4]. Previously, there were 11 cases of nasopharyngeal pleomorphic adenoma reported in a study by Bowman et al and one patient reported by Karligkiotis et al, making a total of 12 cases seen in the literature [2,5]. Pleomorphic adenoma might be mistaken as a malignant neoplasm when it grows at unusual anatomical sites, such as the nasopharynx in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Selten (in etwa 8 %) findet sich diese Entität auch in den kleinen Speicheldrüsen des oberen Respirationstrakts. Mögliche Lokalisationen sind die Mundhöhle, die Nasenhauptund Nasennebenhöhlen, der Pharynx, der Larynx, die Trachea und auch die Tränendrüsen [2,3,4].…”
Section: Diskussionunclassified